2018
DOI: 10.1007/s00167-018-4879-5
|View full text |Cite|
|
Sign up to set email alerts
|

The WOMAC score can be reliably used to classify patient satisfaction after total knee arthroplasty

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 29 publications
4
43
1
Order By: Relevance
“…Pain, for example, was primarily assessed using VAS (visual analog scale) and/or Likert scale [134]. Pain, in association with stiffness was primarily assessed using WOMAC (Western Ontario and McMaster Universities osteoarthritis index) [135], but also KOOS (knee injury and osteoarthritis outcome score) [136], and/or ROM (range of motion) questionnaire [137]. As one of the first of such studies, Trock et al additionally used a modified Ritchie scale to determine joint tenderness [138].…”
Section: Elf-pemf Effects On Osteoarthritismentioning
confidence: 99%
“…Pain, for example, was primarily assessed using VAS (visual analog scale) and/or Likert scale [134]. Pain, in association with stiffness was primarily assessed using WOMAC (Western Ontario and McMaster Universities osteoarthritis index) [135], but also KOOS (knee injury and osteoarthritis outcome score) [136], and/or ROM (range of motion) questionnaire [137]. As one of the first of such studies, Trock et al additionally used a modified Ritchie scale to determine joint tenderness [138].…”
Section: Elf-pemf Effects On Osteoarthritismentioning
confidence: 99%
“…There have been some previously published studies that have reported the concerns of patients before TKA [ 17 19 , 27 ]. However, Chinese patients may differ from other study populations in terms of their concerns and expectations of surgical treatment [ 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcomes were assessed at the final follow-up by an independent examiner (S.P.) who was not involved in surgical procedure and included Harris Hip score (HSS) [14], Western Ontario Mc-Ministry score for the hip (h-WOMAC) [15], Knee Society score (KSS) [16], and Western Ontario Mc-Ministry knee score (k-WOMAC) [17, 18].…”
Section: Methodsmentioning
confidence: 99%